2011
DOI: 10.1021/cn200033j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of the GluA2 AMPA Receptor Channel Opening: The Role of 4-Methyl versus 4-Carbonyl Group on the Diazepine Ring of 2,3-Benzodiazepine Derivatives

Abstract: 2,3-Benzodiazepine derivatives are synthesized as drug candidates for a potential treatment of various neurodegenerative diseases involving the excessive activity of AMPA receptors. Here, we describe a rapid kinetic investigation of the mechanism of inhibition of the GluA2Qflip AMPA receptor channel opening by two 2,3-benzodiazepine derivatives, i.e. the prototypic 2,3-benzodiazepine compound GYKI 52466 [(1-(4-aminophenyl)-4-methyl-7,8-methylenedioxy-5H-2,3-benzodiazepine)] and 1-(4-aminophenyl)-3,5-dihydro-7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(118 citation statements)
references
References 26 publications
10
108
0
Order By: Relevance
“…Based on the fact that BDZ-d showed similar inhibition constants for the closed-channel and the open-channel state of the flip and flop isoforms of GluA2, we concluded that BDZ-d did not discriminate between the flip and flop isoforms of GluA2. This result is consistent with our observation from the study of other 2,3-benzodiazepine compounds for the flip and flop of GluA2, 15,16,33,34 and suggests that the flip/flop sequence cassette most likely is not involved in the site of binding. 15,16,33,34 Apparently, these compounds cannot be used to control the difference in various functional properties between the flip and flop isoforms of GluA2, such as desensitization 35−39 and channel opening reaction.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Based on the fact that BDZ-d showed similar inhibition constants for the closed-channel and the open-channel state of the flip and flop isoforms of GluA2, we concluded that BDZ-d did not discriminate between the flip and flop isoforms of GluA2. This result is consistent with our observation from the study of other 2,3-benzodiazepine compounds for the flip and flop of GluA2, 15,16,33,34 and suggests that the flip/flop sequence cassette most likely is not involved in the site of binding. 15,16,33,34 Apparently, these compounds cannot be used to control the difference in various functional properties between the flip and flop isoforms of GluA2, such as desensitization 35−39 and channel opening reaction.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The fact that BDZ-d inhibited both k cl and k op was consistent with a noncompetitive mechanism of inhibition for BDZ-d acting on the GluA2 AMPA receptor. 15,16,33,34 Together, both the amplitude and rate data from our experiments further clarified that BDZ-d directly inhibits GluA2 AMPA receptor by binding to a noncompetitive site, contrary to what has been perceived. 11,20 BDZ-d Inhibited the Channel Opening of GluA2Q flip by a Two-Step Process.…”
Section: ■ Results and Discussionsupporting
confidence: 46%
See 3 more Smart Citations